2021
DOI: 10.1111/jpn.13527
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of apoptosis‐related gene expression during follicular development in yak

Abstract: The potential reproduction power of domestic animals is limited by a complicated follicular atresia process. P53, caspase-9 (Casp9), Bax, Bcl-2 and Fas play a crucial role in the ovarian mitochondrion-dependent apoptosis and death receptor pathway. In accordance with this study, the expression levels of Casp9, Bax, Bcl-2 and Fas were analysed in ovaries and oviducts of yak by immunohistochemistry (IHC). P53 and the above in ovarian granulosa cells (GCs) from atretic (3-6 mm) to healthy follicles (6-8 mm) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…This result indicated that the expression of VEGFA gene in HF plays a key role in blood vessel generation to maintain the health of the follicles. Meanwhile, the expression of BAX ( 29 ), BCL2 ( 29 , 30 ), CASPASE3 ( 30 ), and CYP19A1 ( 31 ) and the concentration of E2 ( 24 ) and PROG ( 25 ) were significantly different, which is consistent with the results of prior research. All these studies illustrated that the grouping of our study was reasonable.…”
Section: Discussionsupporting
confidence: 89%
“…This result indicated that the expression of VEGFA gene in HF plays a key role in blood vessel generation to maintain the health of the follicles. Meanwhile, the expression of BAX ( 29 ), BCL2 ( 29 , 30 ), CASPASE3 ( 30 ), and CYP19A1 ( 31 ) and the concentration of E2 ( 24 ) and PROG ( 25 ) were significantly different, which is consistent with the results of prior research. All these studies illustrated that the grouping of our study was reasonable.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we can reasonably suppose that the yak follicular fluid exosomes increase 2-OHE 2 secretion through the activation of autophagy and that this may be an effective control method by which to improve the embryo quality and pregnancy rate and have a specific effect on the biological functions of COCs. Previous studies have shown that yak follicles were classified as healthy (6–8 mm) or atretic follicles (3–6 mm) upon examination with a stereoscopic microscope [ 58 ]. Thus, in our study, we selected widely vascularized follicles larger than 8 mm in diameter with a uniform, bright, and translucent appearance.…”
Section: Discussionmentioning
confidence: 99%
“…The oviduct is an important site for fertilization in yaks and previous studies focused on its morphology ( 18 ), POxia-inducible factor-1 alpha ( 19 ), ERK1/2 ( 20 ), estrogen receptor genes ( 21 ), follicle-stimulating hormone receptor (FSHR) gene ( 22 ), DNA damage induced transcript 3 ( 23 ), and apoptosis-related genes in the yak oviduct ( 24 ). There are currently no transcriptomic studies on the different parts of the yak oviduct, and there is a lack of research on the fertilization mechanism from the perspective of mRNA.…”
Section: Discussionmentioning
confidence: 99%